A Congestion Theory of Unemployment Fluctuations - Yusuf Mercan; Benjamin Schoefer; Petr Sedláček (Center for Economic Studies and Ifo Institute (CESifo), 2020)
In recessions, unemployment increases despite the—perhaps counterintuitive—fact that the number of unemployed workers finding jobs expands. On net, unemployment rises only because even more workers lose their jobs. We propose a theory of unemployment fluctuations resting on this countercyclicality of gross flows from unemployment into employment. In recessions, the abundance of new hires “congests” the jobs the unemployed fill, diminishes their marginal product and discourages further job creation. Countercyclical congestion alone explains about 30–40 percent of U.S. unemployment fluctuations. Besides generating realistic labor market volatility, it also provides a unified explanation for the cyclical labor wedge, the excess earnings losses from job displacement and from graduating during recessions, and the insensitivity of unemployment to labor market policies, such as unemployment insurance.
Keywords: E24; J63; J64; 330; unemployment; business cycles; recessions